What Is the Maximum Tibial Tunnel Angle for Transtibial PCL Reconstruction? A Comparison Based on Virtual Radiographs, CT Images, and 3D Knee Models. Issue 5 (13th May 2022) - Teng, Yuanjun; Da, Lijun; Jia, Gengxin; Hu, Jie; Liu, Zhongcheng; Zhang, Shifeng; Han, Hua; Xia, Yayi
Abstract: Background: To minimize the killer turn caused by the sharp margin of the tibial tunnel exit in transtibial PCL reconstruction, surgeons tend to maximize the angle of the tibial tunnel in relation to the tibial plateau. However, to date, no consensus has been reached regarding the maximum angle for the PCL tibial tunnel. Questions/purposes: In this study we sought (1) to determine the maximum tibial tunnel angle for the anteromedial and anterolateral approaches in transtibial PCL reconstruction; (2) to compare the differences in the maximum angle based on three measurement methods: virtual radiographs, CT images, and three-dimensional (3D) knee models; and (3) to conduct a correlation analysis to determine whether patient anthropomorphic factors (age, sex, height, and BMI) are associated with the maximum tibial tunnel angle. Methods: Between January 2018 and December 2020, 625 patients who underwent CT scanning for knee injuries were retrospectively reviewed in our institution. Inclusion criteria were patients 18 to 60 years of age with a Kellgren-Lawrence grade of knee osteoarthritis less than 1 and CT images that clearly showed the PCL tibial attachment. Exclusion criteria were patients with a history of tibial plateau fracture, PCL injuries, tumor, and deformity around the knee. Finally, 104 patients (43 males and 61 females, median age: 38 [range 24 to 56] years, height: 165 ± 9 cm, median BMI: 23 kg/cm 2 [range 17 to 31]) were included for analysis. CT data were used to create virtual 3D knee models, and virtual true lateral knee radiographs were obtained by rotating the 3D knee models. Virtual 3D knee models were used as an in vitro standard method to assess the true maximum tibial tunnel angle of anteromedial and anterolateral approaches in transtibial PCL reconstruction. The tibial tunnel's entry was placed 1.5 cm anteromedial and anterolateral to the tibial tubercle for the two approaches. To obtain the maximum angle, a 10-mm- diameter tibial tunnel was simulated by making the tibial tunnel near the posterior tibial cortex. The maximum tibial tunnel angle, tibial tunnel lengths, and perpendicular distances of the tunnel's entry point to the tibial plateau were measured on virtual radiographs, CT images, and virtual 3D knee models. One-way ANOVA was used to compare the differences in the maximum angle among groups, and correlation analysis was performed to identify the relationship of the maximum angle and anthropomorphic factors (age, sex, height, and BMI). Results: The maximum angle of the PCL tibial tunnel relative to the tibial plateau was greater in the anteromedial group than the anterolateral group (58° ± 8° versus 50° ± 8°, mean difference 8° [95% CI 6° to 10°]; p < 0.001). The maximum angle of the PCL tibial tunnel was greater in the virtual radiograph group than the CT image (68° ± 6° versus 49° ± 5°, mean difference 19° [95% CI 17° to 21°]; p < 0.001), the anteromedial approach (68° ± 6° versus 58° ± 8°, mean difference 10° [95% CI 8° to 12°]; p < 0.001), and the anterolateral approach (68° ± 6° versus 50° ± 8°, mean difference 18° [95% CI 16° to 20°]; p < 0.001), but no difference was found between the CT image and the anterolateral groups (49° ± 5° versus 50° ± 8°, mean difference -1° [95% CI -4° to 1°]; p = 0.79). We found no patient anthropomorphic characteristics (age, sex, height, and BMI) that were associated with the maximum angle. Conclusion: Surgeons should note that the mean maximum angle of the tibial tunnel relative to the tibial plateau was greater in the anteromedial than anterolateral approach in PCL reconstruction, and the maximum angle might be overestimated on virtual radiographs and underestimated on CT images. Clinical Relevance: To perform PCL reconstruction more safely, the findings of this study suggest that the PCL drill system should be set differently for the anteromedial and anterolateral approaches, and the maximum angle measured by intraoperative fluoroscopy should be reduced 10° for the anteromedial approach and 18° for the anterolateral approach. Future clinical or cadaveric studies are needed to validate our findings.